22nd International Conference on Advanced Information Networking and Applications (Aina 2008) 2008
DOI: 10.1109/aina.2008.143
|View full text |Cite
|
Sign up to set email alerts
|

Fairness of High-Speed TCP Stacks

Abstract: We present experimental results evaluating fairness of several proposals to change the TCP congestion control algorithm, in support of operation on high bandwidth-delayproduct (BDP) network paths. We examine and compare the fairness of New Reno TCP, BIC, Cubic, Hamilton-TCP, Highspeed-TCP and Scalable-TCP. We focus on four different views of fairness: TCP-friendliness, RTT-fairness, intraand inter-protocol fairness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…Also, the plots of Figures 3(b), 3(c) and 3(d) are very similar in shape, including peaks an troughs. This is to be expected of BIC and CUBIC, as other studies have showed that they behave similarly [11,12]. Compound TCP's similarity in behaviour is not considered surprising: although BIC and CUBIC respond to loss, loss was not a parameter in our experiments.…”
Section: Self-fairness and Weights W Nsupporting
confidence: 50%
See 2 more Smart Citations
“…Also, the plots of Figures 3(b), 3(c) and 3(d) are very similar in shape, including peaks an troughs. This is to be expected of BIC and CUBIC, as other studies have showed that they behave similarly [11,12]. Compound TCP's similarity in behaviour is not considered surprising: although BIC and CUBIC respond to loss, loss was not a parameter in our experiments.…”
Section: Self-fairness and Weights W Nsupporting
confidence: 50%
“…Our testbed was the well-known dumbbell arrangement (Figure 1), as used in previous similar studies [5,9,12,16]. This simple testbed helps to reduce the factors of error that may affect the results and concentrate on the protocol behaviour.…”
Section: Testbedmentioning
confidence: 99%
See 1 more Smart Citation
“…An implicit assumption in JFI is that all of the processes being measured are equally capable of consuming the resource for which they are competing, and this is indeed the general assumption made in previous work [9], [15], including our own [1], [16]. However, when examining network flows, this is not necessarily true: some protocols may attain better performance than others given the same network conditions.…”
Section: Resource Usage and Relative Capabilitymentioning
confidence: 71%
“…A modified version of BIC, named CUBIC is the default TCP congestion control version in present Linux releases. BIC however may achieve better fairness results towards standard TCP version than CUBIC, as highlighted in [20].…”
Section: Envisaged Tcp Versionsmentioning
confidence: 99%